Antiviral treatment with valacyclovir reduces virus shedding in saliva of Antarctic expeditioners - Mehta, Satish K.; Diak, Douglass M.; Rooney, Bridgette V.; Krieger, Stephanie S.; Nelman-Gonzalez, Mayra; Locke, James P.; Nagel, Maria A.; Young, Millennia; Crucian, Brian E. (Frontiers in Virology, 2023)
Reactivation of herpes viruses such as Epstein-Barr virus (EBV), herpes simplex virus 1 (HSV1), and varicella zoster virus (VZV) increase in astronauts during spaceflight as compared to their preflight and postflight levels. Reactivations can increase the risk of associated clinical conditions like herpes zoster, chronic neuropathic pain, vision loss, stroke, cognitive impairment, and cold sores. Furthermore, continued viral shedding for longer periods after space travel may increase the risk of viral transmission to crew contacts who are uninfected including but not limited to the immunocompromised or newborn infants. Thus, it is essential to develop spaceflight countermeasures to prevent herpes viral reactivations ensuring the health of the crewmembers and their contacts. One such countermeasure is prophylactic administration of an antiviral drug (valacyclovir) against the alpha herpesviruses (VZV, HSV1). To determine the effectiveness of this countermeasure, we studied shedding of EBV, VZV and HSV1 in Antarctic expeditioners who have similar salivary viral shedding patterns during winter-over as astronauts during long spaceflights. Countermeasure efficacy of this antiviral drug was determined by 3 major parameters i) viral load and frequency, ii) physiological stress biomarkers (cortisol, DHEA, and amylase) and iii) immune markers (inflammatory cytokines) during the winter-over in the saliva of expeditioners with and without administration of this drug. Thirty-two volunteers from two Antarctic stations (McMurdo and South Pole) participated in this study. Subjects were randomly assigned to either treatment group (valacyclovir HCl: 1 g/day), or placebo group (oyster calcium 500mg/day). The viral shedding reduced significantly in the treatment group versus the placebo group by >24 fold for EBV and >5 fold for HSV1. No VZV shedding was seen in any of the subjects. 50% of the placebo saliva samples had measurable viral DNA (EBV, HSV1, or both) compared to 19% of the treatment group. There was no significant change in the Cortisol:DHEA or alpha-amylase indicating physiological stress was similar between the groups. No difference was detected in salivary cytokines except IL-10 which was significantly lower in the treatment group. These data indicate that valacyclovir is a safe and successful intervention to reduce herpes virus shedding in individuals subjected to extreme environments and stressors.